PENGARUH PERMINTAAN, PASOKAN, BIAYA KENDARAAN, DAN KONDISI CUACA TERHADAP PENENTUAN HARGA DAUN BAWANG DI PASAR TRADISIONAL PANORAMA - Riski Dwi Utami; Rika Dwi Yulihartika; Ana Nurmalia (Jurnal Saintifik (Multi Science Journal), 2025)
This study aims to determine the relationship between independent variables (demand, supply, vehicle costs, and weather conditions) and the dependent variable (selling price of spring onions) at Panorama Market in Bengkulu City. The sample used consisted of 33 spring onion sellers at Panorama Market, using a saturated sampling method. The data analysis method used was multiple linear regression analysis to determine the correlation between the dependent and independent variables. The results of the study showed that there is a simultaneous influence between the dependent and independent variables. Where the four independent variables have a partial influence on the dependent variable.